Exploring animal welfare through an investigation of veterinary education and on-farm assessments of dairy calf welfare - Shivley, Chelsey B., author; Grandin, Temple, advisor; Garry, Franklyn B., committee member; Engle, Terry E., committee member; Rollin, Bernard E., committee member; Kesel, Martha L., committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.
Keywords: animal welfare judging; dairy calf management; veterinary education; dairy calf average daily gain; animal welfare; dairy calf passive transfer